Fabrication of a Microfluidic System Using Micromolded Alginate Gel as a Sacrificial Material for Tissues Engineering. (29th May 2020) - Wang, Meng; Yang, Xiaoning; Liang, Lanju
Abstract : We described a sacrificial molding for the formation of microfluidic networks. In this molding, the micromolded calcium alginate (Ca-Alg) is introduced as a sacrificial template. The basis of this procedure is fabricating a micromolded Ca-Alg hydrogel and encapsulating this model within a second gel and removing it by ion-exchange to leave a microchannel in the remaining gel. This microfluidic system can readily deliver solutes into the channels and even control the transport of solutes from channels into the bulk of the gels. Furthermore, the perfused vascular channels can sustain the metabolic activity of encapsulated cells, indicating the feasibility of this microfluidic system in the field of tissue engineering.